Upcycling of homogeneous food waste in 3D printing food inks - Lim, Fiona Xin Ying (Nanyang Technological University, 2024)
In this study, we explored various hydrocolloids (sodium alginate, kappa carrageenan, and thermoplastic starch) alongside different food wastes like butterhead lettuce, okara, sesame cake, and brewer’s spent grain to develop food waste inks. Through 3D food printing, rheological tests, and storage tests, we gained insights into viscosity, shear-thinning behaviour, recovery characteristics, and long-term stability of the inks, assessing their impact on printability. We found 5% thermoplastic starch to be the most suitable hydrocolloid base, with the best printing properties observed in 20% w/v butterhead lettuce, 20% w/v sesame cake, 20% w/v brewer’s spent grain, and 10% w/v okara-based ink. The distinct compositions, hydrophilic/hydrophobic nature, and molecular structure of different food wastes influenced interactions and behaviours with 5% thermoplastic starch, affecting their printing properties, rheological characteristics, and storage stability. Our focus on creating valuable products from often-overlooked waste sources aims to contribute to sustainability initiatives in the food industry. We suggest using scanning electron microscopy analysis, evaluating food wastes’ densities, and doing hygroscopicity studies in future research.